Penyamaan kulit ular air warna natural - Bambang Oetojo; Widhiati Widhiati; Hasan Basalamah (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1988)
The porpose of this research was to get natural colour and good quality of snake leather. In pretanning process used Chromoduol G with the Cr2 O3 concentration varied from 0,5 %; 1,0% and 1,5 %. Whereas in tanning process used Irgatan LV varied from 20 % , 25 % ,30 %. Furthermore the snake leather output were visual examined for the color and the quality. Statistical analysis reveals that there is unsignify difference (P ≤0,05) the influence or the use of of Irgatan LV and interaction between Cr2 O3 with Irgatan LV towards the colour and the quality of the snake leather. But there is signify difference (P≤ 0,01) the influence of the use of Cr2O3 towards the colour and the quality of the snake leather. The conclusion of this research is that the use Cr2 O3 of 0,5% and Irgatan LV 25% yield high value for colour and for the quality of the snake leather.This experiments use complete Randomized Design, with 81 pieses of good quality of dried – cured snake skin.